Reivindicación, proximidad y artificio de lo indígena en cuatro novelas colombianas (1924-2007) (2014)
ABSTRACT: In the context of a certain consciusness of the cosmopolitan or contemporary charater in Colombia literature. there is the idea that the regionalist narrative or social realism one of whose representative genres is the indigenist novel - has been left behind. Nevertheless, when reviewing the nacional literary production during the last ninety years on the basis of the concepts upon wich the critical comprehension of the Latin-American indigenism is based, it can be shown that this literary trend remains valid in Colombia due to its dynamictopics and perspectives. The study of four novels that were published in the country between 1924 and 2007 permits us to understand that process.